Vegetative and generative properties of two apple cultivars ‘Galiwa’ and ‘Story Inored’ in a multi-row system - Csihon, A.; Gonda, I.; Holb, I. J. (International Journal of Horticultural Science, 2022)
In a five-year (2015-2019) study, some vegetative and generative peculiarities of two resistant apple cultivars (‘Galiwa’ and ‘Story Inored’) were assessed in a young orchard with a multi-row training system. Based on our research, cv. ‘Galiwa’ showed significantly weaker growth, than cv. ‘Story Inored’, which was manifested in lower trunk cross sectional area (TCSA) and lower tree height. Cultivar ‘Story Inored’ reached the optimal tree height (3.1 m) at the age of four, but cv. ‘Galiwa’ could not achieve it neither in five-year-old trees (2.7 m). Cultivar ‘Galiwa’ showed 28.4-32.6 t/ha calculated average yield, while cv. ‘Story Inored’ produced 41.3-102.7 t/ha. Larger fruit size was found in cv. ‘Galiwa’ (72.7-79.1 mm) and smaller in cv. ‘Story Inored’ (66.9-69.2 mm). The fruit surface color was under 50% for cv. ‘Galiwa’ (43-49%), meanwhile cv. ‘Story Inored’ reached higher coloration (87-93%) and an excellent color intensity (4.8-5.0). Shape of cv. ‘Galiwa’ fruits was rather flat, than globular (0.83-0.84 shape index), as cv. ‘Story Inored’ was more elongated (0.95-1.00 shape index).